석면취급 근로자에서 늑막비후가 폐기능에 미치는 영향 - 김지원; Jee Won Kim; 안형숙; Hyeong Sook Ahn; 김경아; Kyung Ah Kim; 임영; Young Lim; 윤임중; Im Goung Yun (Tuberculosis and respiratory diseases, 1995)
Background: Pleural abnormality is the the most common respiratory change caused by asbestos dust inhalation and also develop other asbestos related disease after cessation of asbestos exposure. So we conducted epidemiologic study to investigate if the pleural abnormality is associated with pulmonary function change and what factors are influenced on pulmonary function impairment. Methods: Two hundred and twenty two asbestos workers from 9 industries using asbestos in Korea were selected to measure the concentration of sectional asbestos fiber. Ouestionnaire, chest X-ray, PFT were also performed. All the data were analyzed by student t-test and chi-square test using SAS. Regressional analysis was performed to evaluate important factors, for example smoking, exposure concentration, period and the existence of pleural thickening, affecting to the change of pulmonary function. Results: 1) All nine industries except two, airborn asbestos fiber concentration was less than an average permissible concentration. PFT was performed on 222 workers and the percentage of male was 88.3%, their mean age was $41{±}9$ years old, and the duration of asbestos exposure was $10.6{±}7.8$ yrs. 2) The chest X-ray showed normal(89.19%), pulmonary Tb(inactive)(2.7%), pleral thickening (7.66%), suspected reticulonodular shadow(0.9%). 3) The mean values of height, smoking status, concentration of asbestos fiberwere not different between the subjects with pleural thickening and others, but age, cumulative pack-years, the duration of asbestos exposure were higher in subjects with pleural thickening. 4) All the PFT indices were lower in the subjects with pleural thickening than in the subjects without pleural thickening. 5) Simple regression analysis showed there was a significant correlation between $FEF_{75}$ which is sensitive in small airway obstruction and cumulative smoking pack-years, the duration of asbestos exposure and the concentration of asbestos fiber. 6) Multiple regression analysis showed all the pulmonary function indices were decreased as the increase of cumulative smoking pack-years and especially in the indices those are sensitive in small airway obstruction. Pleural thickening was associated with reduction in FVC, $FEV_1$, PEFR and $FEF_{25}$. Conclusion: The more concentration of asbestos fiber and the more duration of asbestos exposure, the greater reduction in $FEF_{50}$, $FEF_{75}$. Therefore PFT was important in the evaluation of early detection for small airway obstruction. Furthermore pleural thickening without asbesto-related parenchymal lung disease is associated with reduction in pulmonary function. 연구배경: 석면분진의 흡입으로 인한 호흡기 변화중 가장 조기에 그리고 가장 빈번하게 발견되는 것은 늑막 변화이다. 늑막변화에는 늑막상출액, 늑막반, 미만성늑막섬유화로 분류되기도 하나 일반적으로 늑막비후를 단순히 석면폭로의 지표로 여기고 간과하는 경우가 많다. 그러나 석면에 관련된 질환은 대부분이 만성적이고 뒤에 질환이 발현되는 경우가 빈번하여 늑막변화를 나타내는 근로자에 대한 합리적인 관리와 검사가 필요할 것으로 생각된다. 방법: 석면분진을 취급하는 9개 시업장의 작업장 부서별 석면분진농도를 측정하고 석면을 취급하는 업무에 종사하고 있는 222명을 대상으로 하여 설문조사, 흉부 방사선 사진, 폐기능검사를 실시하여 우리나라 석면 취급 근로자들에서 발생되는 늑막변화에 대한 역학조사와 함께 늑막변화에 따른 폐기능의 변화, 그리고 폐기능의 저하에 미치는 인자들에 대한 조사를 실시 하였고 성적은 SAS을 이용하여 분석하였다. 결과: 1) 조사대상 사업장은 총 9개 였으며 대상 사업장중 1개소를 제외하고는 석면분진 농도는 허용농도 이하였다. 조사대상 근로자중 폐기능 검사를 실시한 222명을 대상으로 하였고 남자가 196명(88.3%), 여자 26명(11.7%)였으며 평균 연령은 $41.9{±}9.8$세 이었고 평균 석면분진 폭로기간은 $10.6{±}7.8$년 이었다. 2) 흉부 방사선 소견상 정상소견을 보인 198명(89.19%), 결핵병변이 관찰된 경우 6명(2.7%), 늑막비후가 보인 경우 17명(7.66%), 망상형 간질성 음영이 의심되는 경우 2명(0.90%)이었다. 3) 늑막비후가 있는 군과 없는 군 사이에 평균신장, 흡연력, 분진농도에는 차이가 없으나, 늑막비후가 없는 군에 비하여 있는군에서 연령, 흡연자의 누적 흡연력, 분진 폭로기간이 유의하게 증가되어 있었다. 4) 늑막비후가 있는 군과 없는 군에서 폐기능의 차이를 보면, 모든 폐기능의 지표에서 늑막비후가 있는 군에서 늑막비후가 없는 군에 비해 유의한 감소를 보였다. 5) 단순회귀분석에서 누적흡연력이 클수록, 폭로기간이 길수록, 그리고 분진농도가 높을 수록 폐기능지표들은 감소하였으며 특히 소기도폐색의 지표인 $FEF_{75}$에서 유의하게 변화하였고 누적흡연력은 $FEF_{50}$의 변화에 유의한 영향을 미쳤다. 6) 다중회귀분석시 폐기능지표등이 누적흡연력이 증가할수록 감소하는 경향을 보였으나 주로 소기도폐색지표에 유의한 감소를 보였으며, 늑막비후가 있는 군에서 없는 군에 비하여 폐기능이 현저히 감소하였다. 결론: 석면 취급 근로자에서 여러가지 폐기능 검사 항목과 석면분진농도등 영향을 미칠수 있는 인자를 조사한 결과 분진폭로농도와 폭로기간에 따라 $FEF_{50}$와 $FEF_{75}$이 특히 민감하게 반응하여 석면에 대한 폐질환의 조기진단을 위하여 도움이 될 것으로 생각되며, 본 연구에서 폐실질병변은 없으나 늑막비후만 관찰되는 경우에도 폐기능이 현저하게 감소한 것으로 미루어 이에 대한 적극적인 관리가 필요하다.